Reporte de Caso de Injuria Renal Aguda por Pancreatitis en Paciente Felino. Informe de Pasantía en una Clínica Veterinaria en Bogotá (2023)
Mascotas club is a veterinary clinic located at Carrera 73B Bis # 6- 22 Su, in the central Kennedy neighborhood, it has 24-hour service, provides general and specialized consultation services, care and hospitalization of dogs and cats, clinical laboratory service, x-rays, ultrasound and endoscopies, as well as general and specific surgery for dogs and cats, is in charge of Dr. Raúl Diaz, his team is made up of 7 veterinarians, 4 assistants, 2 receptionists, 1 General services person and external professionals for the different specialties.